2017
DOI: 10.1177/0269215517723162
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of a randomized, controlled, double-blind study of low-level laser therapy before exercises in knee osteoarthritis: laser and exercises in knee osteoarthritis

Abstract: We find that the immediate post-intervention improvements from LLLT plus strengthening exercises were maintained for six months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 19 publications
5
36
0
3
Order By: Relevance
“…Another non-invasive therapeutical modality that has been used for several years in the control of pain is laser therapy. Its anti-in lammatory effect is pointed out in several studies [1,11,12]. However, in this case study where the therapy used was conjugated, VAS presented a percentage decrease of -716.66% in relation to pain perception.…”
Section: Resultsmentioning
confidence: 56%
“…Another non-invasive therapeutical modality that has been used for several years in the control of pain is laser therapy. Its anti-in lammatory effect is pointed out in several studies [1,11,12]. However, in this case study where the therapy used was conjugated, VAS presented a percentage decrease of -716.66% in relation to pain perception.…”
Section: Resultsmentioning
confidence: 56%
“…This research study suggests that analgesia associated with LLLT results in the anti-inflammatory properties on the articular capsule as suggested by the World Association of Laser Therapy (WALT), with similar results being produced, resulting in both pain relief and a decrease in knee circumference values. [6,7,8] The main finding of this study is that of an adjunctive effect of LLLT with the conservative exercise management of KOA. The findings showed that the KOA outcomes significantly improved across all three intervention groups (p<0.05), with the LLLT group showing better short-term pain relief, but the combined exercise-LLLT group demonstrated better longterm reduction in pain symptoms.…”
Section: Discussionmentioning
confidence: 90%
“…In like fashion the LLLT alone modulates pain and its antiinflammatory effect has been investigated in some studies [7,9]. Even though, the effect of these two modalities acting concomitantly has not been studied before, being a precursor of an innovative equipment.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, laser therapy has been used to modulate pain. The studies are based on the anti-inflammatory effect of light as an explanation for the improvement of pain [7][8][9]. In this Context, the uses of technology as therapy excellent option of treatment propose in reason of necessity of decrease of medicine intake.…”
Section: Introductionmentioning
confidence: 99%